The Effect of Vitamin D Supplements on Antioxidant Parameters of Serum and Saliva in Diabetic Rats - A Tahmasbnezhad; F Asgharpour; S Kazemi; H Gholinia; M Motallebnezhad (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2024)
Background and Objective: Vitamin D deficiency plays an important role in the process of diabetes and it may cause the appearance and exacerbation of symptoms by destroying and inducing different pathways. Vitamin D also has antioxidant properties and inhibits the production of free radicals. Therefore, this study was conducted to determine the role of vitamin D supplements on antioxidant parameters of serum and saliva and to compare them in diabetic rats. Methods: This experimental study was conducted on 28 male Wistar rats that were randomly divided into 4 groups (C group: healthy, CV group: healthy with vitamin D, DC group: diabetic without vitamin D, and DV group: diabetic with vitamin D). Streptozocin (65 mg/kg) was used intraperitoneally to make the rats diabetic. After 10 weeks, saliva (stimulated with pilocarpine) and blood from the eye vein were sampled. The antioxidant level was evaluated by measuring the serum and salivary levels of antioxidant factors (CAT, TAC, SOD, MDA). Findings: Vitamin D injection had a significant effect on salivary SOD level (6.44±1.02 U/ml) and serum TAC level (25862.22±4382.06 µmol/l) (p<0.05). In addition, diabetes decreased the salivary level of CAT and TAC (p<0.001). The findings did not show a significant difference in the serum and salivary levels of MDA. Moreover, vitamin D decreased fasting blood sugar in diabetic rats (211.14±18.9) (p<0.05) and the rats that received vitamin D gained less weight at the end of the study (71.67±13.13 gr). Conclusion: The results of the study showed that oral intake of vitamin D supplement, along with its reducing effect on blood sugar, can reduce the oxidative stress caused by diabetes in serum and saliva levels.